2007
DOI: 10.1142/s0217751x07036774
|View full text |Cite
|
Sign up to set email alerts
|

Matter Localization and Resonant Deconfinement in a Two-Sheeted Space–time

Abstract: In recent papers, a model of a two-sheeted spacetime M4 × Z2 was introduced and the quantum dynamics of massive fermions was studied in this framework. In the present study, we show that the physical predictions of the model are perfectly consistent with observations and most important, it can solve the puzzling problem of the four-dimensional localization of the fermion species in multidimensional spacetimes. It is demonstrated that fermion localization on the sheets arises from the combination of the discret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(68 citation statements)
references
References 36 publications
0
68
0
Order By: Relevance
“…In previous works [15][16][17][18][19], two of the present authors (Sarrazin and Petit) have shown that for a bulk containing at least two parallel 3-branes hidden to each other, matter swapping between these two worlds should occur. The particle must be massive, can be electrically charged 1 or not, but must be endowed with a magnetic moment.…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…In previous works [15][16][17][18][19], two of the present authors (Sarrazin and Petit) have shown that for a bulk containing at least two parallel 3-branes hidden to each other, matter swapping between these two worlds should occur. The particle must be massive, can be electrically charged 1 or not, but must be endowed with a magnetic moment.…”
Section: Introductionmentioning
confidence: 56%
“…Note that the probability does not depend on the neutron spin state by contrast with the magnetic vector potential direction in space. As detailed in previous papers [17,18], the environmental interactions (related to V ± ) are usually strong enough to almost suppress these oscillations. This can be verified by considering Eq.…”
Section: Matter Swapping Between Two Braneworldsmentioning
confidence: 67%
See 3 more Smart Citations